PERANAN PEREMPUAN DALAM PENINGKATAN KUALITAS PENDIDIKAN ANAK DI PROVINSI BALI - Tisnawati, Ni Made (PIRAMIDA; Vol. 6, No.1 Juli 2010)
Balinese woman are still have many weakness, in their economic problem and theparticipation in public decision process. The data in 2006, showed that there are74,8 percent women are unpaid worker. To increase the human development, theroles of woman are need. This aims of this research are to find out the roles ofwomen in children education in Province of Bali. This research is using depthinterview method. The result of this research shown that the roles of women areimportant in increasing the quality of their children education. The ruraldevelopment policy must be based on the women and children welfare.
Keywords: education development, the roles of women, economics contribution